42nd annual AGU hydrology days - American Geophysical Union, author; Colorado State University, author (Colorado State University. Libraries, 2022)
Includes the schedule and presentation abstracts only. The 42nd Annual American Geophysical Union Hydrology Days meeting held on April 25-27, 2022, provides a unique opportunity for students, faculty, staff and practitioners to engage in wide range of water-related interdisciplinary research topics.
Hydrology days 2022
AGU hydrology days 2022
The 42nd Annual AGU Hydrology Days event at Colorado State University was held on April 25-27, 2022 in the Lory Student Center - Grand Ballroom.
Keywords: Hydrology -- Congresses